2018
DOI: 10.1021/acs.jmedchem.7b01558
|View full text |Cite
|
Sign up to set email alerts
|

Binding-Site Compatible Fragment Growing Applied to the Design of β2-Adrenergic Receptor Ligands

Abstract: Fragment-based drug discovery is intimately linked to fragment extension approaches that can be accelerated using software for de novo design. Although computers allow for the facile generation of millions of suggestions, synthetic feasibility is however often neglected. In this study we computationally extended, chemically synthesized, and experimentally assayed new ligands for the β-adrenergic receptor (βAR) by growing fragment-sized ligands. In order to address the synthetic tractability issue, our in silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 64 publications
0
48
0
Order By: Relevance
“…Molecules can be constructed atom-by-atom or by combination of fragments. 13 They can be grown in the context of a binding pocket, [20][21][22][23][24] which allows for structure-based scoring, or be constructed and scored using entirely ligand-based methods. Choosing a very general representation of molecules for construction, such as atom-by-atom and bond-bybond building, allows for potentially exploring all of chemical space.…”
Section: Models For De Novo Molecular Designmentioning
confidence: 99%
“…Molecules can be constructed atom-by-atom or by combination of fragments. 13 They can be grown in the context of a binding pocket, [20][21][22][23][24] which allows for structure-based scoring, or be constructed and scored using entirely ligand-based methods. Choosing a very general representation of molecules for construction, such as atom-by-atom and bond-bybond building, allows for potentially exploring all of chemical space.…”
Section: Models For De Novo Molecular Designmentioning
confidence: 99%
“…Chevillard et al reported the application of their "growing via merging" (GVM) workflow [58] to the design of b2adrenergic receptor antagonists.T he design process began with five core fragments that have experimentally determined b2activity.The five core fragments were docked into an X-ray structure of the receptor using DOCK3.6. [59] TheS EED program [60,61] was then used to place fragments compatible with the reductive amination reaction in the binding site (Figure 17).…”
Section: B2-adrenergic Receptor Ligandsmentioning
confidence: 99%
“…Another scenario in F2L is when the co-crystallization of a fragment hit commonly fails and no structural information about the binding mode is available. In these cases, alternative strategies for F2L process are required where the binding mode of a fragment can be predicted using molecular docking calculations (Kumar et al, 2012;Chevillard et al, 2018;Erlanson et al, 2019) on high-quality three-dimensional structures of the target in apo form or bound to other ligands. When neither of the latter are available, a theoretical model of the target protein can be obtained by homology modeling methods.…”
Section: Molecular Dockingmentioning
confidence: 99%